Transforming growth factor receptor III (Betaglycan) regulates the generation of pathogenic Th17 cells in EAE - Duesman, Samuel J.; Ortega-Francisco, Sandra; Olguin-Alor, Roxana; Acevedo-Dominguez, Naray A.; Sestero, Christine M.; Chellappan, Rajeshwari; De Sarno, Patrizia; Yusuf, Nabiha; Salgado-Lopez, Adrian; Segundo-Liberato, Marisol; de Oca-Lagunas, Selina Montes; Raman, Chander; et al. (Frontiers in Immunology, 2023)
The transforming growth factor receptor III (TβRIII) is commonly recognized as a co-receptor that promotes the binding of TGFβ family ligands to type I and type II receptors. Within the immune system, TβRIII regulates T cell development in the thymus and is differentially expressed through activation; however, its function in mature T cells is unclear. To begin addressing this question, we developed a conditional knock-out mouse with restricted TβRIII deletion in mature T cells, necessary because genomic deletion of TβRIII results in perinatal mortality. We determined that TβRIII null mice developed more severe autoimmune central nervous neuroinflammatory disease after immunization with myelin oligodendrocyte peptide (MOG35-55) than wild-type littermates. The increase in disease severity in TβRIII null mice was associated with expanded numbers of CNS infiltrating IFNγ+ CD4+ T cells and cells that co-express both IFNγ and IL-17 (IFNγ+/IL-17+), but not IL-17 alone expressing CD4 T cells compared to Tgfbr3fl/fl wild-type controls. This led us to speculate that TβRIII may be involved in regulating conversion of encephalitogenic Th17 to Th1. To directly address this, we generated encephalitogenic Th17 and Th1 cells from wild type and TβRIII null mice for passive transfer of EAE into naïve mice. Remarkably, Th17 encephalitogenic T cells from TβRIII null induced EAE of much greater severity and earlier in onset than those from wild-type mice. The severity of EAE induced by encephalitogenic wild-type and Tgfbr3fl/fl.dLcKCre Th1 cells were similar. Moreover, in vitro restimulation of in vivo primed Tgfbr3fl/fl.dLcKCre T cells, under Th17 but not Th1 polarizing conditions, resulted in a significant increase of IFNγ+ T cells. Altogether, our data indicate that TβRIII is a coreceptor that functions as a key checkpoint in controlling the pathogenicity of autoreactive T cells in neuroinflammation probably through regulating plasticity of Th17 T cells into pathogenic Th1 cells. Importantly, this is the first demonstration that TβRIII has an intrinsic role in T cells.